EVALUASI BESAR BUTIR TERHADAP SIFAT MEKANIS CuZn70/30 SETELAH MENGALAMI DEFORMASI MELALUI CANAI DINGIN - Riyan Sanjaya; Eddy S Siradj (Jurnal Ilmiah Teknik Mesin POROS, 2017)
Abstract: The research was conducted because of the many industries that use CuZn 70/30 as a raw material in industrialization. CuZn 70/30 was studied to obtain the strong mechanical properties of brass. Research CuZn 70/30 was evaluated using a process of heating of about 6150 ± 50C and then held for 90 minutes. The next process is the process of cold rolling by using a variety of reduction and then tested by using a Vickers hardness testing, tensile testing, observation of the microstructure. The result of this research is a fine microstructure (below 10 μm), hardness (HV 211.67). Tensile test also conducted to get how much resistance CuZn 70/30 to resist the pull. The cold rolling process causing the decrease the mechanical properties and also increase the plastic properties of the brass.